Kualitas Fisik dan Kimiawi Maggot BSF yang Dibudidaya Oleh Peternak Menggunakan Media Pakan yang Berbeda - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Erwan Erwan; K.G. Wiryawan; Sumiati Sumiati; Moh. Taqiuddin; M.U. Utami; N.P.W.O. Ardyanti (LPPM Universitas Mataram, 2023)
This study aims to determine the physical and chemical quality of maggot cultivated by farmers on the island of Lombok using different feed media. The research was conducted in 2 tages, namely: Phase I. Observation of 5 locations of maggot farms on Lombok Island with a production scale of at least 5 kg per week. The parameters observed were the type of feed used, production scale, body weight and body length of maggot per head. Stage II. Analisis of the nutritional quality of feed and maggot media using the Proximate analysis method. Parameters observed were water content, ash content, crude protein, crude fat, and crude fiber. The data collected were tabulated and discussed descriptively. The results showed that there were 4 TPS locations and 1 quail farm location which was assisted with maggot cultivation with a maggot production scale of 7-350 kg per week. The lowest production scale is at the location of the quail farm using quail manure and the highest scale is at the TPS location Ds. Sengkol using kitchen waste as feed media, expired milk, coconut dregs, and banan stems. The protein content of the feed media that had been converted by maggot ranged from 4.51-24.64% and the maggot content produced ranged from 23.0-42.45%, the highest at quail Farm Puyung village which uses quail waste media. The conclusion of this study that the use of quail waste media as a feed medium resulted in the best quality of maggot.